2016
DOI: 10.3390/info7020026
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Three Computer-Based Communication Activities for Supporting Older Adult Independent Living

Abstract: Abstract:Technology has become an increasingly integral part of life. For example, technology allows individuals to stay in touch with loved ones, obtain medical services through telehealthcare, and enjoy an overall higher quality of life. Particularly for older adults, using technology increases the likelihood that they will maintain their independence and autonomy. Long-distance caregiving has recently become a feasible option where caregivers for older adults can access reports and information about their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recent studies showed that physical exercise programs reduce the risk of falling and improve appreciably the motor functions of the elderly [3][4][5][6] However, motivation to engage in physical exercises is scarce in the elderly [7] and new methods to engage elderly people in physical exercises should be used. Currently, new measurements technologies (portable, inexpensive, with network connectivity, and also for complex body movement [8]) are applied to the field of game and augmented reality [9].…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies showed that physical exercise programs reduce the risk of falling and improve appreciably the motor functions of the elderly [3][4][5][6] However, motivation to engage in physical exercises is scarce in the elderly [7] and new methods to engage elderly people in physical exercises should be used. Currently, new measurements technologies (portable, inexpensive, with network connectivity, and also for complex body movement [8]) are applied to the field of game and augmented reality [9].…”
Section: Related Workmentioning
confidence: 99%
“…Heinz et al implemented and tested tools for computer-based communication activities such as Skype and daily health diary for independent leaving of older adults [ 40 ]. They found tele-healthcare technologies can be a feasible option for monitoring their well-being of older adults, but some people experienced difficulty in testing the tools.…”
Section: Introductionmentioning
confidence: 99%